Diagnostic value of electron microscopy detection using abdominal fat pad biopsy in systemic amyloidosis - Wang, Di; Wang, Yan; Liu, Baojian; Liu, Yingying; Sun, Shiren (Clinical nephrology, 2021)
Electron microscopy (EM) was used to observe the deposition and ultrastructural characteristics of amyloids in abdominal adipose tissue, which provided a reliable basis for pathological diagnosis of systemic amyloidosis. 42 patients with established amyloidosis and 8 controls underwent surgical biopsy of subcutaneous abdominal fat. The fat tissues were submitted concurrently in 4% buffered neutral formalin for histological sections preparation, in glutaraldehyde fixative for EM studies, and in saline solutions for immunofluorescence tests. Light microscopy revealed marked brick-red staining in 11 of 42 samples, 6 moderate and 11 slight staining in the septum of cells, medium and small sized vessel, and apple green double refraction under polarized light microscopy. There were no significant differences in fat biopsies between the systemic amyloidosis and normal subjects in 14 cases. The EM showed approximate 10-nm-thick straight filaments in adipose tissue in all 42 cases with amyloidosis. The positive rate of diagnosis was 100%. Congo red stained sections alone in cases with scant amyloid led to false negative results, but the EM was able to characterize the amyloid protein in all cases. Therefore, preliminary diagnosis of suspected cases can be made by Congo red staining, but the final diagnosis requires an electron microscopic examination.